2020
DOI: 10.3390/ijerph17176126
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Perceived Risks and Benefits of Heroin Use among Young People (18–24 Years) in Mauritius: Economic Insights from an Exploratory Qualitative Study

Abstract: The decreasing age of young people injecting illicit drugs is an under-reported challenge for the prevention of HIV transmission worldwide. Young people aged 15–24 years represent 1 in 5 persons living with HIV in Mauritius where the epidemic is driven by injecting drug use and risky sexual behaviours. We recruited 22 heroin users aged 18–24 and 5 service providers working in harm reduction (HR) for the present study. Qualitative data were collected through unstructured interviews. We adopted an economic frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Reluctance to engage with health care services also contributes significantly to a lack of knowledge of blood-borne diseases among PWID. Inadequate knowledge of the health risks may also contribute to the initiation of drug injection [68]. Several studies have highlighted inadequate knowledge about sterilization practices required to prevent the transmission of blood-borne diseases among PWID [69,70].…”
Section: Risk Perception and Stigma Among People Who Inject Heroinmentioning
confidence: 99%
See 2 more Smart Citations
“…Reluctance to engage with health care services also contributes significantly to a lack of knowledge of blood-borne diseases among PWID. Inadequate knowledge of the health risks may also contribute to the initiation of drug injection [68]. Several studies have highlighted inadequate knowledge about sterilization practices required to prevent the transmission of blood-borne diseases among PWID [69,70].…”
Section: Risk Perception and Stigma Among People Who Inject Heroinmentioning
confidence: 99%
“…In a cohort of homeless individuals injecting drugs, limited awareness of the health risks was evident, as well as steps taken to mitigate risk given their limited circumstances [69]. It has also been shown that a small proportion of heroin users may combine heroin with other drugs which may also increase risks [68].…”
Section: Risk Perception and Stigma Among People Who Inject Heroinmentioning
confidence: 99%
See 1 more Smart Citation